2004
DOI: 10.1161/01.cir.0000124479.89015.64
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Benefits of Left Univentricular Pacing in Patients With Congestive Heart Failure

Abstract: Background-Resynchronization therapy by simultaneous pacing of the right and left ventricles has gained wide acceptance as a useful treatment for patients with severe congestive heart failure. Several short-term hemodynamic studies in humans and animals failed to demonstrate any benefit of biventricular pacing over left univentricular pacing, but long-term studies on this pacing mode are lacking. The objective of this study was to assess the outcome over a 1-year period of patients paced exclusively in the lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 36 publications
5
61
0
Order By: Relevance
“…Experience with chronic biventricular pacing in children is sparse, but a multicenter study showed promising results with regard to cardiac function after 4 months of resynchronization therapy [11], and biventricular pacing proved effective in the treatment of six children with RV pacing-induced heart failure [20]. In adults with congestive heart failure, chronic LV lateral wall pacing (single-site, short AV delay) can be as effective as biventricular pacing [4,12,33]. To our knowledge, the effect of chronic biventricular pacing in children has not been compared with LV lateral wall pacing alone.…”
Section: Relation Between Pacing Site and LV Functionmentioning
confidence: 99%
“…Experience with chronic biventricular pacing in children is sparse, but a multicenter study showed promising results with regard to cardiac function after 4 months of resynchronization therapy [11], and biventricular pacing proved effective in the treatment of six children with RV pacing-induced heart failure [20]. In adults with congestive heart failure, chronic LV lateral wall pacing (single-site, short AV delay) can be as effective as biventricular pacing [4,12,33]. To our knowledge, the effect of chronic biventricular pacing in children has not been compared with LV lateral wall pacing alone.…”
Section: Relation Between Pacing Site and LV Functionmentioning
confidence: 99%
“…24 Other factors will continue to warrant RV lead placement in many patients. Although no LV lead dislodgements were observed in the study by Blanc et al, 23 the incidence has been reported at 5% to 10% in larger studies. 11,25 Patients with poor LV function are at risk for sudden cardiac death from ventricular arrhythmias.…”
mentioning
confidence: 79%
“…3,19 -21 Two small studies suggested that benefit of single site LV pacing is persistent at 4 weeks and 6 months. 17,22 In this issue of Circulation, Blanc and coworkers 23 extend the follow-up observations of single site LV pacing. Functional capacity (6-minute walk and maximal O 2 uptake), ventricular size and function, and blood norepinephrine levels before and after 12 months of left univentricular pacing were evaluated in 22 patients with dilated cardiomyopathy, LBBB, and New York Heart Association class III or IV heart failure.…”
mentioning
confidence: 88%
“…Chronic benefit includes reverse remodeling (21)(22)(23)(24)(25), improved LV function and decreased myocardial oxygen consumption (26). Long term bi-ventricular pacing is associated with a significant reduction in mitral regurgitation jet area (4,27), left ventricular mass, left ventricular end-systolic and end-diastolic dimensions of all indicative reverse remodeling (28)(29)(30).…”
Section: Chronic Effectsmentioning
confidence: 99%